Mitochondrial disorders and drugs: what every physician should know - Daniele Orsucci; Elena Caldarazzo Ienco; Gabriele Siciliano; Michelangelo Mancuso (BioExcel Publishing Ltd, 2019)
Mitochondrial disorders are a group of metabolic conditions caused by impairment of the oxidative phosphorylation system. There is currently no clear evidence supporting any pharmacological interventions for most mitochondrial disorders, except for coenzyme Q10 deficiencies, Leber hereditary optic neuropathy, and mitochondrial neurogastrointestinal encephalomyopathy. Furthermore, some drugs may potentially have detrimental effects on mitochondrial dysfunction. Drugs known to be toxic for mitochondrial functions should be avoided whenever possible. Mitochondrial patients needing one of these treatments should be carefully monitored, clinically and by laboratory exams, including creatine kinase and lactate. In the era of molecular and 'personalized' medicine, many different physicians (not only neurologists) should be aware of the basic principles of mitochondrial medicine and its therapeutic implications. Multicenter collaboration is essential for the advancement of therapy for mitochondrial disorders. Whenever possible, randomized clinical trials are necessary to establish efficacy and safety of drugs. In this review we discuss in an accessible way the therapeutic approaches and perspectives in mitochondrial disorders. We will also provide an overview of the drugs that should be used with caution in these patients.